Unravelling the semiconductor properties of mixed stack donor acceptor cocrystals of pyrene derivatives and TCNQ: effect of crystal packing versus super-exchange mechanism. Issue 37 (7th September 2022) - Mandal, Arkalekha
Abstract : The role of crystal packing and super-exchange mechanism to dictate the semiconductor properties of two mixed DDADDA stack charge transfer cocrystals is elucidated via theoretical study. Abstract : We have discussed the semiconductor properties of two reported 2 : 1 and 1 : 1 charge transfer donor–acceptor cocrystals with mixed ⋯DDADDA⋯ stacking. These cocrystals (CCDC 1212856 and 1212858) are comprised of 2-phenyl-3-(pyrene-2-yl)acrylonitrile (PPA) and 1-(naphthalene-2-yl)-3-(pyrene-1-yl)prop-2-en-1-one (NPPO) as the π-donors and TCNQ as the π-acceptor. The donors have one pyrene moiety which is adjoined to another phenyl/naphthalene ring by a cyano/carbonyl substituted π-linker. The acceptor molecule in the (PPA)2 :TCNQ cocrystal forms π⋯π stacking with a pyrene core, while TCNQ is alternatively π-stacked with pyrene or naphthalene in the NPPO:TCNQ cocrystal. The electronic properties of the mixed stack charge transfer cocrystals are determined by a super-exchange mechanism, i.e., the transfer of a hole (or electron) between donors (or acceptors) through the acceptor (or donor) molecule. The NPPO:TCNQ cocrystal has unique features as the frontier MOs on two different donor moieties take part in the super-exchange mechanism. The difference in the electronic properties of these CT cocrystals has been discussed in terms of three characteristic parameters viz. crystal packing, the degree of charge transfer and the super-exchange mechanism along the direction of mixed π⋯π stacking.